Moralitas Tindakan Ekonomi Pedagang Pasar Kamis Sungai Manau Kabupaten Merangin Provinsi Jambi - Inka Sri Yunara; Nazori Nazori; Nurfitri Martaliah (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2023)
An understanding of morality as distinguished through legality is found in Kant's moral philosophy. Based on his knowledge, morality is the similarity of nature or behavior to inner provisions or laws, namely what Kant sees as "obligations". Morality is always fulfilled if we obey the law outwardly but because we are afraid of an impact of that law outwardly, but because we know that obeying the law is an obligation. In another part, Kant said that there are two parts of the principle that make human action, such as maxims (maxime) and objective rules. Maxims are teachings that are still running subjectively, which are based on subjective vision and form the basis for action. Despite having a mind, the human being as a subject is an imperfect person, and also has passions, emotions, tastes and so on. Basically (basic values) means that the economy is useful for helping economic implementers (in this case traders) will destroy problems (moral) in their economic practices. In general, the market is interpreted as a meeting place for buyers and sellers in carrying out trading activities. However, along with the increasingly dynamic human life, the form and meaning of the market will become broader. This study uses a qualitative descriptive research type, because it seeks to clarify phenomena or events, people, objects or processes that are relevant to the Morality of Economic Actions of Traders in the Thursday Market. The object of this research is traders in the Thursday River Manau market. This study uses primary data and secondary data. Data obtained by means of observation, interviews, and documentation. The results of this study are that traders on Thursday's market understand how to trade properly, in selling we should have to do a good method and it's better for us to avoid lies that can drown us in bad things in the future.